(untitled) (Proceedings of The International Conference on Economics and Development, 2019)
The objective of this study is to investigate what determinant factors affecting capital flow to Emerging markets (EMEs) during Global Financial Crisis (GFC). Whether push factors as external factors or pull factors as domestic / internal factors and what is the most dominant variable using study of literature method. The method used in this study is review of literature, firstly investigate five previous literatures on Latin America and Asia crises and then focus on six main literatures that related to GFC. The findings show the determinant factors affecting capital flow to EMEs during GFC are push factors with world interest rate and global risk condition as main or dominant variables during 2007-2009 episode. Push factors are determinant factors and world interest rate and global risk appetite are dominant variables.